2022
DOI: 10.1021/acs.jnatprod.2c00638
|View full text |Cite
|
Sign up to set email alerts
|

Talaropeptins A and B, Tripeptides with an N-trans-Cinnamoyl Moiety from the Marine-Derived Fungus Talaromyces purpureogenus CX11

Abstract: We report the discovery of talaropeptins A (1) and B (2), tripeptides with an unusual 5/6/5 heterocyclic scaffold and an N-trans-cinnamoyl moiety, which were identified from the marine-derived fungus Talaromyces purpureogenus CX11. A bioinformatic analysis of the genome of T. purpureogenus CX11 and gene inactivation revealed that the biosynthesis of talaropeptins involves a nonribosomal peptide synthase gene cluster. Their chemical structures were elucidated using a combination of 1D and 2D NMR spectroscopy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Talaropeptin A 16 is a metabolite of marine-derived Talaromyces purpureogenus CX11. 14 Analysis of the biosynthetic gene cluster and gene inactivation has shown that the biosynthesis of talaropeptin A 16 involves a nonribosomal peptide synthase gene cluster.…”
mentioning
confidence: 99%
“…Talaropeptin A 16 is a metabolite of marine-derived Talaromyces purpureogenus CX11. 14 Analysis of the biosynthetic gene cluster and gene inactivation has shown that the biosynthesis of talaropeptin A 16 involves a nonribosomal peptide synthase gene cluster.…”
mentioning
confidence: 99%
“…245 Talaverrucin A 764, a heterodimeric oxaphenalenone with a unique 6/6/6/5/5/5/6 fused ring system, was isolated from an Antarctic spongederived strain of Talaromyces. 246 Other Talaromyces strains yielded a diverse range of metabolites including thioestercontaining benzoate derivatives 765-770, 247 sulfur containing spiro alkaloid 771, unusual diacid 772 and alkaloids 773-777, 248 aromatic polyketides 778-782, 249 tripeptides 783 and 784, containing an N-trans-cinnamoyl group, 250 A machine learning-augmented density functional theory method (DU8ML) was utilised to revise the stereochemistry of tersone E to 815, which is identical to the terrestrial fungal metabolite citridone A. 3 Structural revision of penipacids A-E, originally isolated from Penicillium paneum, from amidines to hydrazones 816-820 through total synthesis also raised the possibility that they may be Schiff base adduct artefacts produced through conjugation with a putative NP precursor, the hydrazine N-aminoanthranilic acid with diacetone alcohol under extraction conditions.…”
Section: Cyanobacteriamentioning
confidence: 99%
“…245 Talaverrucin A 764 , a heterodimeric oxaphenalenone with a unique 6/6/6/5/5/5/6 fused ring system, was isolated from an Antarctic sponge-derived strain of Talaromyces . 246 Other Talaromyces strains yielded a diverse range of metabolites including thioester-containing benzoate derivatives 765 – 770 , 247 sulfur containing spiro alkaloid 771 , unusual diacid 772 and alkaloids 773 – 777 , 248 aromatic polyketides 778 – 782 , 249 tripeptides 783 and 784 , containing an N-trans -cinnamoyl group, 250 chlorinated unsaturated alcohol 785 and coumarin derivative 786 , 251 decalin derivatives 787 and 788 , 252 meroterpenoid 789 (ref. 253) and oligophenalenone 790 and 791 and xanthoradone 792 dimers.…”
Section: Marine Microorganisms and Phytoplanktonmentioning
confidence: 99%
“…The HMBC and ROESY correlations showed the amino acid sequence as cin-Ser-Ala-Pro. The relative configurations of the stereogenic carbons in 20 were determined as 8R*,10R*,15S*,16S* by ROESY correlations while their absolute configurations were established as 8R,10R,15S,16S by Marfey's analysis and comparison of the calculated and experimental ECD spectra [44].…”
Section: Linear Tripeptidesmentioning
confidence: 99%
“…This hypothesis was supported by a comparison of the calculated and experimental ECD spectra. The structures of 20 and 21 suggested that their biosynthesis is carried out predominantly by NRPS machinery [44].…”
Section: Linear Tripeptidesmentioning
confidence: 99%